In vitro HIV DNA integration in STAT3 drives T cell persistence-A model of HIV-associated T cell lymphoma. - Michael Rist; Machika Kaku; John M Coffin (PLoS Pathogens)
Oncogenic retroviruses are known for their pathogenesis via insertional mutagenesis, in which the presence of a provirus and its transcriptional control elements alter the expression of a nearby or surrounding host gene. There are reports of proviral integration driving oncogenesis in people with HIV and the use of HIV-derived vectors for gene therapy has raised concern about oncogenic side effects. To study this issue, we used an in vitro primary human CD4 + T cell infection model developed in our laboratory to identify HIV-1 integration sites that might influence cell proliferation or survival. Combining integration site analysis and bulk RNA sequencing, we found that an upregulated STAT3 signature due to proviral insertional mutagenesis was associated with persistent HIV-infected CD4 + T cells. HIV+ persistent cells also expressed a STAT3-related anti-apoptotic and cytotoxic phenotype that resembles that of HIV-associated T cell lymphomas. HIV insertional mutagenesis of STAT3 and expression of its downstream targets provides a model of HIV-associated T cell lymphomas that can be used to further determine the oncogenic drivers of HIV-associated lymphomas, both AIDS- and gene therapy-associated, and, potentially, to evaluate therapeutics against these HIV-associated cancers.